2010
DOI: 10.1007/s00296-010-1406-5
|View full text |Cite
|
Sign up to set email alerts
|

Sexual functions in ankylosing spondylitis

Abstract: Ankylosing spondylitis (AS) is a chronic inflammatory disorder of the axial skeleton. In recent years, several authors reported an increased prevalence of sexual dysfunction among AS patients. We aimed to find out, whether the prevalence of erectile dysfunction among AS patients is different from age-matched healthy controls. Thirty-seven male patients with AS who were diagnosed according to the modified New York criteria and 67 normal healthy controls (NHC) were included in this study. Clinical characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
56
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 15 publications
(19 reference statements)
4
56
1
Order By: Relevance
“…Three of these studies concluded that sexual function was significantly affected by AS. [9,13,14] In our study, we used the IIEF scale, and our results were in line with the study done by Bal et al [12] We found no significant difference in sexual functions between the male patients with AS and the healthy controls, but the sexual drive domain of the IIEF was slightly lower in those with AS. However, this difference was not at a significant level.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Three of these studies concluded that sexual function was significantly affected by AS. [9,13,14] In our study, we used the IIEF scale, and our results were in line with the study done by Bal et al [12] We found no significant difference in sexual functions between the male patients with AS and the healthy controls, but the sexual drive domain of the IIEF was slightly lower in those with AS. However, this difference was not at a significant level.…”
Section: Discussionsupporting
confidence: 80%
“…The IIEF scoring scale was used in two previous studies. [9,12] Pırıldar et al [9] reported that all domains of the IIEF, except for sexual drive, were significantly lower in male patients with AS than in the healthy control group, and Bal et al [12] could not find any significant differences in terms of the IIEF, except for the sexual drive domain. Three of these studies concluded that sexual function was significantly affected by AS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Pirildar et al compared AS male patients' erectile functions with healthy controls and found significantly higher frequency of ED in AS patients, in which the duration of morning stiffness was found to be the only clinical feature related to ED. 6 Bal et al 29 found significant difference only in sexual desire domain of International Index of Erectile Function scoring system, duration of morning stiffness and BASDAI was negatively correlated with sexual desire and overall satisfaction. Dincer et al 8 also reported significantly lower sexual drive, problem assessment and low overall satisfaction scores in AS patients compared with healthy controls.…”
Section: Discussionmentioning
confidence: 95%